Catalytic combustion of diesel soot over K/Ag substituted LaCoO3 perovskite catalysts - Mishra A.; Prasad R. (My University, 2025)
To control soot emissions exhaust after treatment has been paid much attention. Present paper deals with the preparation (by sol-gel method) and characterization (by XPS and BET surface area) of the K/Ag substituted LaCoO3 and pure LaCoO3 perovskite catalyst and their activities towards the diesel soot oxidation at practical conditions. Catalytic oxidation of soot was studied under tight contact with soot/catalyst ratio of 1/10. A bed of 110 mg of soot-catalyst mixture was made over glass wool in a tubular reactor and oxidation of soot was carried out with a flow rate of air at 150 ml/min and rate of heating was maintained at 1°C/min with the help of a microprocessor based temperature controller. The oxidation products were analyzed for CO2 and CO by an online gas chromatograph equipped with porapak Q-column, methaniser and FID detector. Activity of the catalyst for soot oxidation was evaluated on the basis of light off temperature characteristics Ti, T50 and T100 where, Ti, T50 and T100 are temperature corresponding to the start of soot ignition, the 50% conversion of soot and total oxidation of soot respectively. Three catalysts LaCoO3, La0.9K0.1CoO3 and La0.9Ag0.1CoO3 were tested for soot oxidation. La0.9K0.1CoO3 Perovskite catalyst was found to give best result than pure LaCoO3 and Ag substituted LaCoO3 for soot oxidation with light off temperatures Ti= 233°C, T50 = 267°C, T100=291°C. © Research India Publications.